Postpartum psychological distress after emergency team response during childbirth. (2nd October 2019) - Silverstein, R. Gina; Centore, Michael; Pollack, Andrea; Barrieau, Gabrielle; Gopalan, Priya; Lim, Grace
Abstract: Purpose: To evaluate the feasibility and acceptability of a protocol determining the relationship between emergency team response (ETR) during childbirth and acute stress disorder (ASD) and post-traumatic stress disorder (PTSD) symptoms. Methods: In a prospective, observational, cohort design, women experiencing ETR during childbirth were approached and recruited on postpartum day-1 and followed for six weeks. Demographics, obstetric and birth characteristics, ASD scores and PTSD scores (by Impact of Events Scale, IES and PCL-civilian) were recorded. Recruitment and retention rates were recorded, and scores were compared to women who did not experience ETR. Results: Three hundred sixty-nine were approached and 249 were enrolled (67.5% recruitment rate). One hundred twenty-five completed all procedures (50.2% retention). Twenty experienced ETR (3.5% event rate), 12 enrolled (60.0% recruitment rate) and 8 completed the study (66.7% retention). The ETR group had higher PCL and IES scores (PCL: ETR median 12, non-ETR median 2, p  = .08; IES: ETR median 22.5, non-ETR median 20, p  = .08). ASD scores were similar between groups. Conclusions: Methodology investigating the link between ETR and postpartum psychological distress is feasible and acceptable. A relationship between ETR and PTSD symptoms appears to exist, with ETR being associated with higher PTSD scores compared to non-ETR childbirths. Methods that incorporate awareness of the unique concerns of vulnerable populations are needed.